Social power and willingness to share knowledge / Norfadzilah Abdul Razak, Sharifah Fazirah Syed Ahmad and Zulkefli Abd Rahman - Abdul Razak, Norfadzilah; Syed Ahmad, Sharifah Fazirah; Abd Rahman, Zulkefli (Universiti Teknologi MARA, Shah Alam, 2018)
Willingness to share knowledge is subjective to an individual. It relies on an individual’s decision to share or not with others. One of the factors that influence individual willingness to share knowledge is authority ranking. There are four types of social power comprising legitimate, coercive, referent and expertise power. Among of these four types of social power, this study aimed to investigate the significant relationship of social power and willingness to share knowledge. A survey was conducted among 150 knowledge workers in ICT industries which are mainly located in Cyberjaya, Malaysia. Partial Least Square analysis was conducted to analyze measurement and structural model. The results of the study indicate that none of the social power dimensions influence willingness to share knowledge as in the Malaysia context.